Monitoring Cerebral Oxygenation in Neonates: An Update - Dix, Laura Marie Louise; van Bel, Frank; Lemmers, Petra Maria Anna (Frontiers in Pediatrics, 2017)
Cerebral oxygenation is not always reflected by systemic arterial oxygenation. Therefore, regional cerebral oxygen saturation (rScO2) monitoring with near-infrared spectroscopy (NIRS) is of added value in neonatal intensive care. rScO2 represents oxygen supply to the brain, while cerebral fractional tissue oxygen extraction, which is the ratio between rScO2 and systemic arterial oxygen saturation, reflects cerebral oxygen utilization. The balance between oxygen supply and utilization provides insight in neonatal cerebral (patho-)physiology. This review highlights the potential and limitations of cerebral oxygenation monitoring with NIRS in the neonatal intensive care unit.